Analisis Strategi Pemasaran Ekowisata Green Hill Park Taman Wisata Alam Cimanggu Kabupaten Bandung – Jawa Barat - astutik, yuli; najib, mukhamad (IPB University, 2016)
Indonesia has a high potential for nature tourism refer to the increasing number of tourist visited. Green Hill Park is a tourism area at TWA Cimanggu, Bandung District, West Java. The aim of this study is to identify the internal and external factors, analyze the application of ecotourism principles, as well as analyze and arrange ecotourism marketing strategies at Green Hill Park TWA Cimanggu. Principles of ecotourism has become the cornerstone of tourism activities implementation in Green Hill Park, but has not been applied properly because of the unstable management. Based on the results of IFE and EFE, Green Hill Park was in a strong enough position. Based on the IE matrix, Green Hill Park was located on the second cell, grown and built. Based on the SWOT analysis, six alternative strategies were obtained. Based on the analysis of AHP, the most influential factor is community participation, factors that play the biggest role are managers, objective that most needed to be achieved was to increase tourism services by using the priority alternative strategies which is involving the community in the tourism program.